Interpretasi Gestur Tubuh Tokoh Arjuna dalam Lukisan Wayang Kamasan Berdasarkan Pendekatan Semiotika Roland Barthes - Argiyanti, Ni Kadek Pradnya; Anggreswari, Ni Putu Yunita; Ramadiansyah, Sahri Aflah; Haes, Putri Ekaresty (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the meaning of body gestures in the depiction of Arjuna within the Kamasan Wayang paintings using Roland Barthes’ semiotic approach. The Kamasan Wayang painting, a traditional Balinese art form, is rich in philosophical and symbolic meanings reflecting moral, heroic, and spiritual values of Balinese society. The research employs a qualitative descriptive method with semiotic analysis focusing on Barthes’ two levels of meaning: denotation and connotation. The findings reveal that Arjuna’s gestures in Kamasan paintings convey not only aesthetic beauty but also profound moral and social messages. The upright posture with folded hands symbolizes self-control, loyalty, and wisdom, while the eye direction represents harmony between strength and gentleness. Overall, Kamasan Wayang serves as a cultural text that embodies ethical and spiritual values in Balinese life. Thus, Barthesian semiotics effectively reveals the deeper meanings behind traditional visual symbols.